The Influence of the Implementation of Eazy Passport Innovation and Excellent Service on Employee Performance - RUSTOMO TOMO (Jurnal Ilmu Ekonomi dan Bisnis, 2022)
Abstract The purpose of this study was to determine and analyze the effect of implementing the easy passport innovation and excellent service on employee performance both partially and simultaneously during the Covid-19 pandemic from various limitations. This type of research is descriptive quantitative explanatory research is a research method that intends to explain the position of the variables studied and the influence between one variable and another. The entire population used as a sample (census) as many as 38 people with the status of ASN/PSN at the Immigration Office Class I Non TPI Karawang, considering the number of ASN/PNS was small. The data collection technique of this research conducted through interviews, questionnaires, and documentation studies. The results showed that partially and simultaneously there was a positive and significant effect on the implementation of easy passport innovation and excellent service on employee performance at the Immigration Office Class I Non TPI Karawang. Hope that innovation and service will given more attention if the Covid-19 pandemic still hits Indonesia and the world in general. Keywords: Innovation, service, performance during the pandemic